Migration status and HIV risk perception in metropolitan areas of Gauteng Province - Motlhale, Melitah (My University, 2017)
Background Risk perception has serious implications for health if the risk assessment informing the risk perception is accurate and well-reasoned. Gauteng Province is characterised by a high concentration of migrants and this sub-population may find themselves in compromising conditions that might heighten their risk of contracting HIV. HIV risk perception research in South Africa has been carried out on several high-risk populations but not among migrants. The aim of this study was to examine the association between migration status and HIV risk perception as well as to identify the factors associated with HIV risk perception among migrants and non-migrants in Metropolitan areas of Gauteng Province in 2012. Methods This was a secondary data analysis of data collected from a cross-sectional household survey that was conducted to explore the needs and vulnerabilities of the poor urban groups residing in the Metropolitan Municipalities of Gauteng Province in 2012. A total of 1 834 respondents made up of non-migrants, internal and international migrants qualified for this study. Pearson’s chi-square test was used to assess the association between migration and HIV risk perception. Unadjusted and adjusted logistic regression models were fitted to identify factors associated with HIV risk perception. Results Of the total respondents, 55% considered themselves not to be at risk of HIV infection. There was a strong statistical association between migration status and HIV risk perception (p-value = 0.001). Internal migrants (50.4%) were more likely to perceive themselves as being at risk than international migrants (43.4%) and non-migrants (40.3%). Using the 95% Confidence Interval, from the adjusted logistic regression; age (AOR = 0.97; CI: 0.96, 0.98), Metropolitan area (AOR = 1.31; CI: 1.02, 1.68), common perceived health problem as HIV or TB (AOR = 2.03; CI: 1.55, 2.65) and accessibility to HIV information and treatment (AOR = 0.65; CI: 0.45, 0.98) were associated with HIV risk perception. Conclusion This study showed low HIV risk perception among residents of Gauteng Metropolitan area. There is a strong association between migration status and HIV risk perception. Low risk perception despite the presence of HIV risk factors suggests the need for programmes aimed at creating awareness about HIV and promoting adoption of preventive health lifestyle among migrants and non-migrants in Gauteng Metropolitan area.
A Research Report submitted to the Faculty of Health Sciences in Partial fulfilment of the Requirements for the Degree of Master of Science in Epidemiology in the field of Epidemiology and Biostatistics, school of Public Health. The University of the Witwatersrand. Johannesburg, November 2017.
Keywords: HIV